Model of valorization of soils under viewpoint of their potential resistance against some selected contaminants: (based on the author’s PhD thesis) - Sandner, Jan (Studia Ecologiae et Bioethicae, 2004)
The progressing process of industrialization poses a greater and greater threat to the natural environment, especially agricultural land. To determine the balance of this environment, it is necessary to study the impact of these pollutants and to determine the so-called This paper tries to solve the problems of impact assessment by creating the so-called environmental algorithm, in which all the basic components of the soil environment are taken into account, for the simulation of pollutant emissions. The necessary calculations were made using modern calculation techniques in the Information Center SGGW-AR. Defining these soil relationships is the basis for constructing models that will objectively define the actual state of "soil resistance to contamination". These models should become the basis for planning plant production for areas with a higher degree of risk, and also affect the still current problem of stereotypical testing of soil suitability for agricultural production, known as "soil valuation"